Hakim Konstitusi di Persimpangan Jalan: Kuasa Lembaga Pengusul dalam Pemberhentian yang Kontroversial - Isthifailla, Isthifailla; Pratama, Agung Barok (Sharia Faculty, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The process for selecting Constitutional Court judges involves three branches of government: the House of Representatives (legislative), the President (executive), and the Supreme Court (judicial). This arrangement is intended to ensure integrity, independence, and proper oversight. Normatively, neither the House of Representatives, the President, nor the Supreme Court has the authority to dismiss a Constitutional Court judge they have proposed. However, on September 29, 2022, the House of Representatives removed Judge Aswanto from the Constitutional Court, citing his frequent annulment of legislation enacted by the House of Representatives as the reason. This study aims to analyze the dismissal of Constitutional Court judges by the proposing institution. It employs a normative legal research method, utilizing legislative, case, and conceptual approaches. The findings indicate that Judge Aswanto's dismissal was inconsistent with Article 23, paragraph (4) of the Constitutional Court Law, which stipulates that